Polish Auxiliary Forces and their Law Academic Scripts at the University Camp in Grangeneuve/Fribourg - Leraczyk, Izabela (Acta Universitatis Lodziensis. Folia Iuridica, 2022)
The soldiers of the 2nd Division of Rifle Infantry interned in Switzerland in the years 1940–1945 were offered an opportunity to undertake studies on the grounds of cooperation between war camps and Swiss academies. Among the study programs organized at the University Camp in Grangeneuve/Fribourg were studies in law. Their syllabus included subjects taught at the University of Fribourg and provided for lectures on Polish law. The aim of the article is to demonstrate the role that the law academic scripts (course materials) played in the camp. The article includes a brief explanation of what the scripts were and outlines the origin of the series entitled Scripts of University Lectures in Grangeneuve, later Fribourg – La Chassotte (Skrypty wykładów uniwersyteckich w Grangeneuve). They were authored, to a large degree, by soldiers themselves, together with pre-war academics based on Polish universities, graduates in law and practitioners of law. An excellent illustration of their involvement can be the script written in the winter of 1941 by Jan Świda, related to the basic institutions of Swiss inheritance law. The content of this work and the way it was prepared will be compared with the scripts created by Aleksander Mełeń and Wacław Petsch, printed in the same year.